Ҳамза Ҳәкимзада Ниязийдиң тәлим-тәрбиялық ой-пикирлери (SCIENCE and SOCIETY, 2024)
The article discusses the educational-pedagogical activities and educational views of the great pedagogue H.H. Niyazi.